Duración y Probabilidad de Salida del Desempleo: Un estudio para el caso ecuatoriano (2003-2006) con datos de secciones cruzadas repetidas - González , Gabriela (2006)
The present work studies the effect of unemployment's duration and other individual characteristics on the probability of leaving 1t in the Ecuadorian labor market between February 2003 and January 2006. The results show an inverse relationship between the duration and the probability of leaving unemployment up to the fifth quarter; yet, starting with the sixth quarter the relation becomes direct. Furthermore, 1t is shown that women, people who are married, those with a lower educational level, those with a child at home, and people between 20 and 50 years old constitute the demographic group with the larger probability of leaving unemployment. Finally, because some of these people cease to search for a job, a larger probability of leaving unemployment does not necessarily imply a larger probability of actually getting a job.